2023
DOI: 10.1097/hjh.0000000000003380
|View full text |Cite
|
Sign up to set email alerts
|

Estimating mean population salt intake using spot urine samples in Nepal: a cross-sectional study

Abstract: Introduction:Little is known about the usefulness of spot urine testing compared with 24-h urine samples to estimate salt intake in low-income settings. This is given 24-h urinary collection can be costly, burdensome, and impractical in population surveys. The primary objective of the study was to compare urinary sodium levels (as an estimate of salt intake) of Nepalese population between 24-h urine and spot urine using previously established spot urine-based equations. Additionally, this study explored the 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…The results demonstrate clearly that there is a wide variation between salt intake based on 24-h urine collection and that indicated by spot urine irrespective of which equation is used. The authors conclude that none of the spot urinebased equations accurately corresponded to 24-h salt intake in their study [1].…”
mentioning
confidence: 82%
“…The results demonstrate clearly that there is a wide variation between salt intake based on 24-h urine collection and that indicated by spot urine irrespective of which equation is used. The authors conclude that none of the spot urinebased equations accurately corresponded to 24-h salt intake in their study [1].…”
mentioning
confidence: 82%
“…The earlier findings of this dataset reported that the Nepalese population had a much higher salt intake, measured at 13.28 g/day using the 24-hour (24 h) urinary excretion method [ 13 ]. Alternative methods, such as the spot urine method, were noted to have limitations for estimating 24 h salt intake in Nepal [ 14 ]. The primary objective of the present study was to assess the association between salt-related knowledge, attitudes, and behaviours (KAB) and 24 h urinary salt excretion.…”
Section: Introductionmentioning
confidence: 99%